2012
DOI: 10.1016/j.visres.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling fMRI measurements of decreased blood flow in primary visual cortex correlates with decreased visual function in human glaucoma

Abstract: Purpose Altered metabolic activity has been identified as a potential contributing factor to the neurodegeneration associated with primary open angle glaucoma (POAG). Consequently, we sought to determine whether there is a relationship between the loss of visual function in human glaucoma and resting blood perfusion within primary visual cortex (V1). Methods Arterial spin labeling (ASL) functional magnetic resonance imaging (fMRI) was conducted in ten participants with POAG. Resting cerebral blood flow (CBF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 65 publications
(70 reference statements)
5
22
1
Order By: Relevance
“…19 A recent study reported reduction in the resting CBF in the primary visual cortex and its correlation with the loss of visual function in patients with POAG. 44 These findings are evidence of widespread involvement of the cerebrovascular system in glaucoma. It has, however, remained unclear whether and how cerebral vascular changes contribute to the brain neurodegeneration in glaucoma.…”
Section: Discussionmentioning
confidence: 85%
“…19 A recent study reported reduction in the resting CBF in the primary visual cortex and its correlation with the loss of visual function in patients with POAG. 44 These findings are evidence of widespread involvement of the cerebrovascular system in glaucoma. It has, however, remained unclear whether and how cerebral vascular changes contribute to the brain neurodegeneration in glaucoma.…”
Section: Discussionmentioning
confidence: 85%
“…Duncan et al demonstrated that POAG had decreased cerebral blood flow in the visual cortex,17 suggesting that regional metabolism and blood flow contribute to the phenomenon. Li et al also found significantly decreased ALFF/fALFF values in the visual cortices in POAG 12.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent VBM studies have demonstrated a significant reduction in either GM volume (Chen et al, 2013a;Zikou et al, 2012) or density (Boucard et al, 2009;Li et al, 2012) in the V1 and V2 areas. Furthermore, lesions on the visual cortex were also shown in functional MRI (Duncan et al, 2007;Qing et al, 2010), resting blood perfusion (Duncan et al, 2012), experimental animal models (Lam et al, 2009;Yucel et al, 2003) and postmortem histological examinations (Gupta et al, 2006). However, the majority of these studies have mainly focused on GM atrophy or functional defects in the advanced or severe stages of disease, rather than on the progressive changes that occur in the visual cortex.…”
Section: Discussionmentioning
confidence: 99%